Considerations for extracellular vesicle and lipoprotein interactions in cell culture assays. Issue 4 (31st March 2022) - Busatto, Sara; Yang, Yubo; Iannotta, Dalila; Davidovich, Irina; Talmon, Yeshayahu; Wolfram, Joy
Abstract: With an exponential increase in extracellular vesicle (EV) studies in the past decade, focus has been placed on standardization of experimental design to ensure inter‐study comparisons and validity of conclusions. In the case of in vitro assays, the composition of cell culture media is important to consider for EV studies. In particular, levels of lipoproteins, which are critical components of the interstitial fluid, should be taken into consideration. Results from this study reveal that lipoprotein levels in cell culture medium impact the effects that EVs have on recipient cells. Additionally, evidence of EV binding and fusion to lipoprotein‐like structures in plasma is provided. However, it is unclear whether the impact of lipoproteins in cell culture is due to direct interactions with EVs, indirect effects, or a combination of both mechanisms. Taken together, cell culture studies performed in the absence of physiological levels of lipoproteins are unlikely to reflect interactions that occur between EVs and recipient cells in an in vivo environment.